2013
DOI: 10.3136/fstr.19.547
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Rice Stem Extracts Obtained by Subcritical Water/Ethanol Treatment

Abstract: Rice straw stem was treated with subcritical water, ethanol, or a mixture at 170℃ to 230℃. The yield, total carbohydrate content, UV-Vis absorption spectra, phenolic content, radical scavenging activity, and HPLC analysis of the extracts were determined. Higher stem extract yield and total carbohydrate content were achieved when the stem was treated using a subcritical ethanol/water mixture with high ethanol content and at the higher temperature. A maximum yield and total carbohydrate content of 0.387 ± 0.004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Researchers have studied on adding ethanol into water as a modifier to increase the solubility of low-polarity bioactive compounds such as phenolic compounds in subcritical water (Tangkhavanich et al 2013). Adding ethanol in subcritical water may adversely affect the extractability of carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied on adding ethanol into water as a modifier to increase the solubility of low-polarity bioactive compounds such as phenolic compounds in subcritical water (Tangkhavanich et al 2013). Adding ethanol in subcritical water may adversely affect the extractability of carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…4,25,31,32) Figure 3 shows two curves obtained from the relationship between the total phenolic content and DPPH radical scavenging ability; one for the extracts obtained by the subcritical aqueous ethanol treatment, and the other for the extracts obtained by the subcritical aqueous acetone treatment. These data suggest that one of the sources for the antioxidative ability of the extracts obtained by using subcritical aqueous ethanol or acetone were phenolic compounds.…”
Section: )mentioning
confidence: 99%
“…Meanwhile, the negative quadratic coefficient of 2 indicated that the opening of equation parabola was downward. The increment of TPC was limited; even the ratio of solvent/solid ratio was further increased as shown in Runs 11,12,18, and 19 listed in Table 1. The response surface for TPC by varying extraction time and microwave power is shown in Figure 4.…”
Section: The Influence Of the Extraction Parameters On The Totalmentioning
confidence: 95%
“…A higher temperature allows better transfer of active components into the solvent. It was found to result in the decreasing surface tension and viscosity of the solvent at a higher temperature in the subcritical state [18]. The contour plots, a graphical representation of a response surface, were drawn to study the influences of the independent variables and the corresponding effect on the response.…”
Section: The Influence Of the Extraction Parameters On The Extractionmentioning
confidence: 99%